2016
DOI: 10.1061/(asce)su.1943-5428.0000168
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Low-Cost Satellite-Based Geodetic Monitoring over Short Baselines

Abstract: The use of geodetic techniques, in particular of the global positioning system (GPS), or other global navigation satellite systems (GNSS), for monitoring different kinds of deformations is a common practice. This is typically performed by setting a network of geodetic GPS/GNSS receivers, allowing accuracies in the order of millimeters. The use of lower-cost devices has been recently studied, showing that good results can be achieved. In this paper, the impact of the software used for the data analysis is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 23 publications
1
37
0
1
Order By: Relevance
“…Furthermore, two experiments carried out in the Alps, provided a first, satisfactory guess of the accuracy of low-cost, single frequency receivers in landslide monitoring [15]. A recent research is presented also in [16]: in this case, the accuracy of low-cost receivers is assessed for local monitoring by processing daily sessions: accordingly to the baseline length, the final accuracy range from 1 mm (very short baseline) to 1 cm (30 km long baseline).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, two experiments carried out in the Alps, provided a first, satisfactory guess of the accuracy of low-cost, single frequency receivers in landslide monitoring [15]. A recent research is presented also in [16]: in this case, the accuracy of low-cost receivers is assessed for local monitoring by processing daily sessions: accordingly to the baseline length, the final accuracy range from 1 mm (very short baseline) to 1 cm (30 km long baseline).…”
Section: Introductionmentioning
confidence: 99%
“…goGPS and Bernese apply their PPP algorithms in two different ways: Bernese implements a leastsquares post-processing adjustment of all observations collected during a given time period (in this case, daily) to jointly estimate coordinates and ZTD parameters, and goGPS adopts an extended Kalman filter. It should be noted that Caldera et al (2016) already validated goGPS against Bernese with regard to precise relative positioning (Teunissen and Kleusberg 1998;Hoffman-Wellenhof et al 2001) and demonstrated that the two software packages reach the same millimeter level of accuracy. goGPS and Bernese were run using the same processing parameters where possible: GPS-only observations, ionosphere-free combination of L1 and L2 observations, 10 • for the satellites elevation cutoff, global mapping function (Böhm et al 2006), tropospheric gradient not estimated, I08.ATX PCO/PCV model, solid Earth tides model according to IERS convention, and ocean loading model FES2004.…”
Section: Experimental Setup and Data Processingmentioning
confidence: 99%
“…Moreover, Unmanned Aerial Vehicles (UAVs) have gained popularity amongst landslide researchers, combined with photogrammetric applications [12][13][14], whilst Global Position System (GPS) surveying, even if intrinsically a point-wise technique requiring a careful selection of the points to be monitored, represents a benchmark technique in slope monitoring [15][16][17]. This also holds true considering the potential of the endless upcoming of low-cost GNSS receivers, which will probably make GNSS monitoring even more popular in the next future, due to the high-quality performances of new devices [18][19][20][21].…”
Section: Introductionmentioning
confidence: 84%